2020
DOI: 10.1029/2020jc016276
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study of the Effect of Surface Waves on Heat and Momentum Transfer at High Wind Speeds

Abstract: This paper describes laboratory experiments (using a high‐speed wind‐wave flume) of the effects of water waves on heat and momentum exchange in the near‐water atmospheric boundary layer at high wind speeds. Different from previous experiments of this type, the parameters of waves were controlled by a net stretched along the entire channel to effectively decrease the fetch. This helped to achieve dependency of the transfer coefficients on two independent parameters, namely, the wind speed and fetch (expressed v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It should also be emphasized that the growth in the dependence of the enthalpy exchange coefficient on wind speed is significantly weaker than that observed in the laboratory experiments reported in [38,42]. This result needs further study and may be associated with the different features of laboratory and field conditions.…”
Section: Enthalpy Parameters Retrievalmentioning
confidence: 76%
See 3 more Smart Citations
“…It should also be emphasized that the growth in the dependence of the enthalpy exchange coefficient on wind speed is significantly weaker than that observed in the laboratory experiments reported in [38,42]. This result needs further study and may be associated with the different features of laboratory and field conditions.…”
Section: Enthalpy Parameters Retrievalmentioning
confidence: 76%
“…In this paper, we propose the application of a modified profiling method based on the use of data not from the region of constant fluxes but from the wake part. We applied this method (in earlier work) to the results of laboratory modeling [18,38], and the method was used further to retrieve dynamic parameters in tropical cyclones [34]. In the present study, we have expanded the dataset (including the consideration of the data from CBLAST), and, in addition, we modified the profiling method to retrieve the thermodynamic parameters (Section 4).…”
Section: Drag Coefficient and Dynamic Speed Retrievalmentioning
confidence: 99%
See 2 more Smart Citations
“…Bi et al [14] used offshore tower observation and found C d peaked at 18 m s −1 and decreased afterward, but leveled off when larger than 27 m s −1 . Other studies with various methods generally also found the same feature that C d decreased or leveled off with wind speed when it was larger than around 30 m s −1 (e.g., [15][16][17][18][19][20][21][22][23][24]).…”
Section: Introductionmentioning
confidence: 75%